Contributions to early HIV diagnosis among patients linked to care vary by testing venue - Trott Alexander T; RN Dana; RN DeAnna; Lindsell Christopher J; Lyons Michael S; Fichtenbaum Carl J (BMC, 2008)
Abstract Objective Early HIV diagnosis reduces transmission and improves health outcomes; screening in non-traditional settings is increasingly advocated. We compared test venues by the number of new diagnoses successfully linked to the regional HIV treatment center and disease stage at diagnosis. Methods We conducted a retrospective cohort study using structured chart review of newly diagnosed HIV patients successfully referred to the region's only HIV treatment center from 1998 to 2003. Demographics, testing indication, risk profile, and initial CD4 count were recorded. Results There were 277 newly diagnosed patients meeting study criteria. Mean age was 33 years, 77% were male, and 46% were African-American. Median CD4 at diagnosis was 324. Diagnoses were earlier via partner testing at the HIV treatment center (N = 8, median CD4 648, p = 0.008) and with universal screening by the blood bank, military, and insurance companies (N = 13, median CD4 483, p = 0.05) than at other venues. Targeted testing by health care and public health entities based on patient request, risk profile, or patient condition lead to later diagnosis. Conclusion Test venues varied by the number of new diagnoses made and the stage of illness at diagnosis. To improve the rate of early diagnosis, scarce resources should be allocated to maximize the number of new diagnoses at screening venues where diagnoses are more likely to be early or alter testing strategies at test venues where diagnoses are traditionally made late. Efforts to improve early diagnosis should be coordinated longitudinally on a regional basis according to this conceptual paradigm.